Health Impacts and Medical Interventions on Physical Violence Among Adolescents: A Review And Strategies in Indonesia - Sinaga, Nur Flora Nita TB; Tedyanto, Eric Hartono; Rehatta, Nancy Margarita (Faculty of Medicine-Universitas Airlangga, 2025)
Introduction: Violence against adolescents is a global public health issue with significant impacts on physical and psychological health. Data shows that many children around the world experience physical, sexual, or emotional violence, with a high prevalence in Indonesia. Based on data from the 2013 Child Violence Survey, violence against adolescents in Indonesia remains very high, with significant impacts on their physical and psychological health, as well as their academic performance. Objective: This study aims to identify the causes of violence, including family dynamics, social media, and mental health, as well as its impacts, such as health disorders and decreased academic performance. Review: Various factors causing physical violence among adolescents in Indonesia include family influence, social media, and peers. The impact is very detrimental, both in the short and long term, both in terms of physical and mental health. The findings indicate the need for early intervention and additional education in schools to effectively address adolescent violence. The synergy between various disciplines at the Faculty of Medicine is key to creating evidence-based prevention strategies. To mitigate the negative impact, additional education in schools and early interventions involving various disciplines are greatly needed. The synergy between educational programs, government policies, and social support is key to preventing violence. With the strengthening of legal protection, as well as increased attention from parents and the social environment, it is hoped that a safer environment for teenagers can be created. Summary: Overall, this review emphasizes the importance of holistic interventions involving families, schools, and communities to address violence among adolescents and improve their quality of life. There is a need for preventive efforts that involve education in schools, family interventions, and stricter government policies. The success of preventing and addressing physical violence among adolescents heavily relies on the collaboration of all parties involved.